1992
DOI: 10.1159/000168454
|View full text |Cite
|
Sign up to set email alerts
|

Role of Creatine Phosphokinase in Predicting Acute Renal Failure in Hypocalcemic Exertional Heat Stroke

Abstract: Recruits frequently develop hypocalcemia in exertional heat stroke (ExHS) with rhabdomyolysis and acute renal failure (ARF) from intensive training. It usually indicated severe skeletal muscle damage. However, the relative risk of ARF in ExHS patients complicated with hypocalcemia was unknown. The present study was undertaken to evaluate the value of peak serum creatine phosphokinase (CPK) level in predicting ARF in ExHS patients with hypocalcemia. Sixty-eight army recruits with ExHS were hospitalized at the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Higher levels of CK and LDH are compatible with labor under conditions of physical overload and hydro-electrolyte imbalance, as evidenced in several studies [25], [26]. LDH and CK are biomarkers of muscular damage and may increase during situations of intense exercise, in which cell membranes become more permeable and enzymes are released into the interstitial matrix and reabsorbed via the lymphatic system to enter the bloodstream [26].The observation that CK remained high, even in blood samples measured 60 hours after exercise suggests a state of persistent hyperCKemia, much like that which occurs in athletes [26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Higher levels of CK and LDH are compatible with labor under conditions of physical overload and hydro-electrolyte imbalance, as evidenced in several studies [25], [26]. LDH and CK are biomarkers of muscular damage and may increase during situations of intense exercise, in which cell membranes become more permeable and enzymes are released into the interstitial matrix and reabsorbed via the lymphatic system to enter the bloodstream [26].The observation that CK remained high, even in blood samples measured 60 hours after exercise suggests a state of persistent hyperCKemia, much like that which occurs in athletes [26].…”
Section: Discussionmentioning
confidence: 65%
“…Although serum sodium is a less sensitive marker, the lower sodium and calcium levels observed during the harvest period can arise due to possible hydro-electrolyte disturbances associated with intense sweating and the intake of large quantities of water, which could explain the higher frequency of reported cramping in this period [25], [27]. Another study [28] reported the occurrence of hyponatremia among military personnel during intensive training, due to excessive water intake.…”
Section: Discussionmentioning
confidence: 99%
“…ExHS in military recruits is not uncommon in Taiwan [9] despite several preventive measures being carried out. The present study evaluated patients with RBD early in the course of heat injury after exertion, as evidenced by the magnitude of the hyperphosphatemia and hypo calcemia, compared to the other reports [4,5], The re sults demonstrated hypocalcemia, decreased serum l,25(OH)2D levels and decreased ratio of l,25(OH)2D to 25(OH)D during the oliguric phase of ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of the central nervous system are common with confusion, ataxia, convulsions, or prolonged unconsciousness. Complications include hemorrhage, acute renal failure, rhabdomyolysis, liver failure, central nervous system damage, peripheral neuropathy, cardiac conduction abnormalities, a hypodynamic cardiac response, hypocalcaemia, and adult respiratory distress syndrome [Shibolet et al, 1967;Vertel and Knochel, 1967;Sohal et al, 1968;Kew et al, 1970Kew et al, , 1971O'Donnell and Clowes, 1972;Bouges et al, 1987;Shapiro and Seidman, 1990;Shieh et al, 1992]. None of these complications occur in heat exhaustion, which is caused primarily by dehydration [Donoghue et al, 2000;Donoghue, 2003].…”
Section: Introductionmentioning
confidence: 99%